EFECTIVIDAD DE LA POLÍTICA PENITENCIARIA EN LOS CENTROS DE REHABILITACION SOCIAL Y RESPONSABILIDAD DEL ESTADO CONSTITUCIONAL DE DERECHOS - Tandazo Gallegos, Nery Martin (2019)
The present thesis entitled: “EFFECTIVENESS OF PENITENTIAL POLICY IN THE CENTERS OF SOCIAL REHABILITATION AND RESPONSIBILITY OF THE CONSTITUTIONAL STATE OF RIGHTS”, is the result of a deep study of the current problem from the prison crisis that the penitentiary system in Ecuador is experiencing; for having caused riots in some centers of maximum security, reaching the extreme of originating murders against persons deprived of liberty; by other inmates who are members of gangs or mafias who have directed inside the country's prisons, through organized crime; that has seen and patience of the competent authorities, did not try in time to stop this problem; the Executive arriving to Decree the State of Exception, and to limit the rights of persons deprived of liberty to apply a new criminal policy for the national social rehabilitation system, which must be restructured; considering new models of the prison system applied in other laws and dictating new public policies that help to improve the treatment axes to achieve the end of the prison sentence that consists in the social reintegration of the person deprived of liberty. It has failed in Ecuador, new models must be considered that restructure from the authorities that are obliged to guarantee the human rights of the persons deprived of liberty, as well as of the personnel of the penitentiary surveillance body responsible for internal security in each prison center and that are nearby of inmates every day, knowing their needs that must be brought to the immediate attention of the Director of the Center and in turn to the Judge of Penitentiary Guarantees; to solve the problems in law. Remember that the Ecuadorian State is responsible for the custody of the security and human 5 rights of persons deprived of liberty, and if they suffer violations they must respond from the President of the Republic, Ministers, Prosecutors, Judges, Police, Body of Penitentiary Surveillance; Directors of Centers, Ombudsman, Ombudsman, Public, among other authorities that have not responded to the urgent needs of the Social Rehabilitation system. Although we are immersed in a Constitutional State of Rights and Justice, constitutional norms must prevail over internal norms to guarantee the direct and immediate application of the fundamental rights enjoyed by persons deprived of liberty; as a guarantee of human security so that society can live in peace, tranquility, and security, avoiding all types of criminal offenses that injure legal assets protected by the state. . In the present work of legal research during its development materials and methods were applied, in addition techniques of surveys and interviews were applied, results that served to formulate a project of legal reform to the Integral Criminal Organic Code, to guarantee the human rights of private persons of freedom and that those responsible for non-observance be repressed and forced to compensate for negligence in their functions of central government and decentralized autonomous governments.